What are the barriers to teaching computational thinking? - Muilu, Mikko (2021)
Computers were popularized about 40 years ago in the ’80s and the internet 20 years ago in the early 2000s, but the consistent implementation of computer science (CS) is still in early stages in many primary and middle schools (Eickelmann and Vennemann 2017, 733-761). National curricula include computational thinking (CT) and information and communication technology (ICT), but only a few have practical implementation guidelines for them (Bour-geois, Birch, and Davydovskaia 2019). The digital transformation taking place everywhere and in every work area requires new competencies for everyone (Sousa and Rocha 2019, 327-334). The sooner schools adapt to the demand for new skills, the better. For middle school students to understand and learn programming logic, primary and elementary schools should first teach computational thinking and other basic skills. The National curricula of every country under the scope of this research mention ICT, CS and CT (Bour-geois, Birch, and Davydovskaia 2019), but the content and implementation is left for teachers to decide according to the interviewees in this study (Finland, Estonia, Germany, and Greece, ten teachers each). Without unambiguous definitions and guidelines, implementation varies a lot between schools and even between teachers. For example, in the Estonian curriculum, digital competence is one of the mandatory general competencies that schools must develop in the pupils (Lauringson and Rillo 2015). However, most interviewed Estonian teachers say that in order to carry this out, they need more allocated time, resources, and teacher education. This study aims to understand the most common barriers to teaching computational thinking in Europe. A total of 41 teachers from four different countries were interviewed about teaching CT and other computer skills. The most common barriers found in all countries were lack of time, lack of teacher education, lack of material, and lack of resources. Student motivation and student skill heterogeneity were among the new barriers found. The results vary between countries.